Heat Acclimation Does Not Modify Q10 and Thermal Cardiac Reactivity - Kampmann, Bernhard; Bröde, Peter (Frontiers in Physiology, 2019)
Heat acclimation (HA) is an essential modifier of the physiological strain when working or exercising in the heat. It is unknown whether HA influences the increase of energy expenditure (Q10 effect) or heart rate (thermal cardiac reactivity TCR) due to increased body temperature. Therefore, we studied these effects using a heat strain database of climatic chamber experiments performed by five semi-nude young males in either non-acclimated or acclimated state. Measured oxygen consumption rates (VO2), heart rates (HR) and rectal temperatures (Tre) averaged over the third hour of exposure were obtained from 273 trials in total. While workload (walking 4 km/h on level) was constant, heat stress conditions varied widely with air temperature 25-55 °C, vapor pressure 0.5-5.3 kPa, air velocity 0.3-2 m/s. HA was induced by repeated heat exposures over a minimum of three weeks. Non-acclimated experiments took place in wintertime with a maximum of two exposures per week. The influence of Tre and HA on VO2 and HR was analyzed separately with mixed model ANCOVA. Rising Tre significantly (P<0.01) increased both VO2 (by about 7 % per degree increase of Tre) and HR (by 39-41 bpm per degree Tre); neither slope nor intercept depended significantly on HA (P>0.4). The effects of Tre in this study agree with former outcomes for VO2 (7%/°C-increase corresponding to Q10=2) and for HR (TCR of 33 bpm/°C in ISO 9886). Our results indicate that both relations are independent of HA with implications for heat stress assessment at workplaces and for modeling heat balance.